2013
DOI: 10.1002/ece3.511
|View full text |Cite
|
Sign up to set email alerts
|

Human disturbance and stage‐specific habitat requirements influence snowy plover site occupancy during the breeding season

Abstract: Habitat use has important consequences for avian reproductive success and survival. In coastal areas with recreational activity, human disturbance may limit use of otherwise suitable habitat. Snowy plovers Charadrius nivosus have a patchy breeding distribution along the coastal areas on the Florida Panhandle, USA. Our goal was to determine the relative effects of seasonal human disturbance and habitat requirements on snowy plover habitat use. We surveyed 303 sites for snowy plovers, human disturbance, and habi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 48 publications
0
39
0
1
Order By: Relevance
“…). Organisms may be susceptible to disturbance because human activity may be difficult to predict (Webber, Heath & Fischer ) or formerly reliable cues that animals use to assess habitat quality may not be indicative of human disturbance (i.e. an ecological trap; Schlaepfer, Runge & Sherman ).…”
Section: Introductionmentioning
confidence: 99%
“…). Organisms may be susceptible to disturbance because human activity may be difficult to predict (Webber, Heath & Fischer ) or formerly reliable cues that animals use to assess habitat quality may not be indicative of human disturbance (i.e. an ecological trap; Schlaepfer, Runge & Sherman ).…”
Section: Introductionmentioning
confidence: 99%
“…A further consideration is that occupancy is assumed to be static during the designated sampling period (assumption of closure; MacKenzie et al, 2002), and the length of this period may vary depending upon the species and biological timeframe of interest (e.g., the breeding season; Webber, Heath & Fischer, 2013). There are a number of studies that provide theoretical background to study design using an occupancy-modelling framework, highlighting the importance of balancing temporal and spatial replication to most efficiently achieve defined objectives (MacKenzie & Royle, 2005; Bailey et al, 2007; Guillera-Arroita, Ridout & Morgan, 2010; Guillera-Arroita & Lahoz-Monfort, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Future studies should therefore examine whether measures of individual fitness also change along a gradient of urbanization (Chace and Walsh, 2006). Further, birds can shift habitat associations as the breeding season progresses (Betts et al, 2008;Webber et al, 2013). For example, Betts et al (2008) demonstrated that Black-throated Blue Warblers (Setophaga caerulescens) occupy higher quality habitat as the breeding season progresses, and Webber et al (2013) showed that Snowy Plovers (Charadrius nivosus) resettle away from human disturbance during the breeding season.…”
Section: Discussionmentioning
confidence: 95%
“…Further, birds can shift habitat associations as the breeding season progresses (Betts et al, 2008;Webber et al, 2013). For example, Betts et al (2008) demonstrated that Black-throated Blue Warblers (Setophaga caerulescens) occupy higher quality habitat as the breeding season progresses, and Webber et al (2013) showed that Snowy Plovers (Charadrius nivosus) resettle away from human disturbance during the breeding season. Further inference could therefore be gained by examining within-season resettlements of birds in urban areas during the breeding season (McClure and Hill, 2012) and determining whether birds resettle in areas of higher quality.…”
Section: Discussionmentioning
confidence: 96%